Geranium rubricum (Geraniaceae), a new species from ultramafic soils in the Red Hills, northern South Island, New Zealand - Heenan, Peter B; Courtney, Shannel P (Phytotaxa, 2017)
A new species, Geranium rubricum, is described from the Red Hills, northern South Island, New Zealand. Geranium rubricum is distinguished by its rhizomatous and compact growth habit, small and coriaceous leaves up to 10 mm in diameter, large sepals with uniformly sized appressed hairs, and large flowers up to 25 mm in diameter. G. rubricum is restricted to soils associated with ultramafic rock outcrops and scree slopes. It is known from seven small subpopulations in the Red Hills, and the conservation status is assessed using the New Zealand Threat Classification System as Nationally Endangered.